2013
DOI: 10.1155/2013/742476
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity ofCocos nuciferaHusk Fibre: Further Studies

Abstract: In this study, the antimalarial and toxicity potentials of husk fibre extracts of five Nigerian varieties of Cocos nucifera were evaluated in vitro. The only active extract fraction, West African Tall (WAT) ethyl acetate extract fraction, was then evaluated for its phytochemical constituents, antimalarial and toxicity potentials at varying doses (31.25–500 mg/kg body weight) using various organ function indices. The results revealed that WAT ethyl acetate extract fraction (WATEAEF) contained alkaloids, tannins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, parasitemia varied on days 8 and 10, and results with WATEAEF were no better than with chloroquine. Additionally, treatment with 250 and 500 mg/kg body weight WATEAEF significantly increased (P<0.05) plasma creatinine concentration compared with controls ( 65 ). Despite the reduction in parasitemia, the extract cannot yet be considered an appropriate treatment for malaria.…”
Section: Methodsmentioning
confidence: 91%
“…However, parasitemia varied on days 8 and 10, and results with WATEAEF were no better than with chloroquine. Additionally, treatment with 250 and 500 mg/kg body weight WATEAEF significantly increased (P<0.05) plasma creatinine concentration compared with controls ( 65 ). Despite the reduction in parasitemia, the extract cannot yet be considered an appropriate treatment for malaria.…”
Section: Methodsmentioning
confidence: 91%
“…Research has demonstrated the presence of metabolites such as polyphenols, glycosides, steroids, alkaloids, terpenoids, and others which could be responsible for those activities (Renjith et al 2013;Manalo et al 2017;Oliveira et al 2009;Singla et al 2011;Soumya et al 2014). More specifically, the husk extracts of C. nucifera have shown to have antimalarial properties when tested in vitro and in vivo (Adebayo et al 2012;Adebayo et al 2013;Balogun et al 2014;Angeles et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenol-artesunate hybrids Recently, we synthesized antimalarial hybrid compounds from artesunate and some polyphenols present in Cocos nucifera husk, the decoction of which is used for the treatment of malaria in indigenous medicine in Nigeria (Adebayo et al 2012(Adebayo et al , 2013. The compounds synthesized were artesunate-ellagic acid and artesunateprocyanidin hybrid compounds with a ratio of 1:1 of the components in each hybrid compound (Adebayo et al, unpublished; Balogun et al, unpublished).…”
Section: Synthesis Of Hybridsmentioning
confidence: 99%